Controlling procesów jako narzędzie zarządzania ryzykiem - Nowosielski, Stanisław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The report presents the substance and the aims of processing management. It also shows controlling's role and tasks in the particular stages of this management. The report describes the essence and the aims of risk management in the processes. It shows the tasks of a manager and the processing team in the successive stages of risk management. The report submittes the role of the processing controller in the risk management. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 272-281